MEMANFAATKAN IRIGASI SEBAGAI SUMBER ENERGI LISTRIK MIKROHIDRO DI SINGOSAREN WUKIRSARI BANTUL JOGJAKARTA - Suyanto, Muhammad; Subandi, Subandi (Dharma: Jurnal Pengabdian Masyarakat, 2020)
The development of contemporary technology provides a variety of environmental impacts, both positive and negative. This is a logical consequence of every development of life for people both in rural and urban areas, through the Tri Dharma for universities, a lecturer should do community service. Community service taking tofik Utilizing Irrigation as a Micro Hydro Energy Source in Singosaren Wukirsari Imogiri Bantul, Jogjakarta. Sources of electric power are a basic human need in meeting their daily needs, so that electricity plays a very important role in technological developments and future developments. The plant specifications are planned to be adjusted to the water discharge capacity and irrigation flow speed, with a capacity of 1000VA, frequency of 50 Hz, output voltage of 220 Volt with a rotation of 1500 rpm. The voltage generated is a 1-phase AC alternating voltage. With the existence of a micro hydro generator in Wukirsari Village, it will have a positive impact on the community, as a means of lighting for public roads so that the security can be maintained.